A rare case report on bacterial meningitis in second trimester of pregnancy: Review of literature (Indian Journal of Case Reports, 2026)
Bacterial meningitis in pregnancy is a rare but life-threatening condition with significant maternal and fetal risks. A 25-year-old multigravida at 16 weeks of gestation presented with fever, headache, vomiting, and photophobia. Clinical examination revealed meningeal signs and focal neurological deficits. Laboratory findings and cerebrospinal fluid analysis confirmed acute bacterial meningitis. The patient was managed with prompt intravenous antibiotics, corticosteroids, and supportive care under a multidisciplinary approach. She showed marked clinical improvement and was discharged with continuation of pregnancy. Early diagnosis and timely management are crucial to improving outcomes in such cases.